Visions of the periphery: the migrants in the construction of Teresina in the 1970s (Tempo e Argumento, 2009)
This paper is a reflection about Teresina, the state capital of Piauí, in the 1970s, when the city goes through multiple and varied interventions, having the state as its main agent. Such interventions attracted people coming from small towns in Piauí and from other states, who dreamed of job opportunities, formal education, housing, and health care. But on their arrival they found themselves without financial resources to rent a place to live, and occupied areas considered to be of risk as well as public land, a factor that, afterward, the excluding and modernizing process was to determine their moving out to the outskirts of town, then without any basic infra-structure (water and sewage systems, electric energy, telephone service, public transportation or street paving). This transference and its implications to the affected people were taken as the main focus of this paper.
Keywords: Teresina; modernization; memory; migrants